(untitled) (Acta Entomologica Serbica, 2022)
The North American aphid Rhopalosiphoninus latysiphon (Davidson, 1912) (Hemiptera: Aphididae) was found in Serbia for the first time. It is a polyphagous species, mainly feeding on roots, bulbs and tubers. This cryptic living species was detected in yellow water traps on fields of the Institute of Field and Vegetable Crops, Novi Sad (Rimski Šančevi) during the monitoring of aphid flight activity in sugar beet. In total, three specimens were trapped in 2019 and 2020. The main morphological and biological characteristics of the species are given in the text.